2020
DOI: 10.1042/bsr20190318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hnRNPA2/B1 on the proliferation and apoptosis of glioma U251 cells via the regulation of AKT and STAT3 pathways

Abstract: Abstract Glioma is the most common malignant tumor in the human central nervous system. Although heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNPA2/B1) was previously presumed to be a tumor-promoting gene, the relationship between hnRNPA2/B1 and glioma is unclear. Targeting hnRNPA2/B1 interference in glioma cells can significantly inhibit proliferation and increase apoptosis of human glioma cells in vitro. In a tumor xenograft model, knockdown of hnRNPA2/B1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…While hnRNPA1 and hnRNPA2/B1 have been widely studied, studies on hnRNPA0 and hnRNPA3 are limited. Notably, hnRNPAB and its subgroups are closely associated with malignant biological behaviors such as proliferation and apoptosis reduction, as well as poor patient prognosis in various cancer types (16)(17)(18)(19)(20)(21). Our previous study confirmed the upregulation of hnRNPAB expression in CRC tissues compared with adjacent tissues, which was closely associated with poor prognosis (21).…”
Section: Microrna-8063 Targets Heterogeneous Nuclear Ribonucleoprotein Ab To Inhibit the Self-renewal Of Colorectal Cancer Stem Cells Viamentioning
confidence: 55%
“…While hnRNPA1 and hnRNPA2/B1 have been widely studied, studies on hnRNPA0 and hnRNPA3 are limited. Notably, hnRNPAB and its subgroups are closely associated with malignant biological behaviors such as proliferation and apoptosis reduction, as well as poor patient prognosis in various cancer types (16)(17)(18)(19)(20)(21). Our previous study confirmed the upregulation of hnRNPAB expression in CRC tissues compared with adjacent tissues, which was closely associated with poor prognosis (21).…”
Section: Microrna-8063 Targets Heterogeneous Nuclear Ribonucleoprotein Ab To Inhibit the Self-renewal Of Colorectal Cancer Stem Cells Viamentioning
confidence: 55%
“…demonstrated that HNRNPA2B1 can mediate the packaging of miR-30b-3p into extracellular vesicles and promotes the ability of GBM cells to resist TMZ ( 148 ). It was also shown that knockdown of HNRNPA2B1 in GBM cells could lead to the inactivation of AKT and STAT3 signaling pathways in tumor cells, reduce the expression of Bcl-2 and PCNA, and thus inhibit the growth of GBM cells, and the establishment of xenograft tumor models using GBM cells with knockdown of HNRNPA2B1 also revealed that knockdown of HNRNPA2B1 could inhibit the progression of GBM in vivo ( 149 ). Analysis of GBM samples with different m6A scores using K-M analysis showed that overall survival was significantly higher in the group with low m6AScore than in the group with high m6AScore, while the P-value for m6AScore was lower than 0.05 (HR>1) in both uni- and mul-tivariate Cox analysis.…”
Section: M6a Modification and Glioblastomamentioning
confidence: 99%
“…Downregulation of hnRNP A2/B1 expression in the glioma cell line U251 further induced apoptosis of tumour cells. They found that the regulation of proliferation and apoptosis of glioma cells was mainly achieved by regulating AKT and TAT3 signalling pathways [ 47 ].…”
Section: Introductionmentioning
confidence: 99%